2019
DOI: 10.1080/14693062.2019.1635874
|View full text |Cite
|
Sign up to set email alerts
|

Conditional nationally determined contributions in the Paris Agreement: foothold for equity or Achilles heel?

Abstract: The Paris Agreement's success depends on parties' implementation of their Nationally Determined Contributions (NDCs) towards the Paris Agreement's goals. In these climate action plans, most developing countries make their mitigation and adaptation contributions conditional upon receiving international support (finance, technology transfer and/or capacity building). While provision of support for NDC implementation could enhance equity among countries, the feasibility of NDC implementation might be challenged b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
44
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 88 publications
(46 citation statements)
references
References 26 publications
0
44
0
2
Order By: Relevance
“…King, 2016;Levin et al, 2015;. Moreover, the relatively positive responses on technical and financial support provided to developing countries to implement their NDCs are quite different from, for instance, Pauw, Castro, Pickering, and Bhasin (2019a), whose work suggested that current financing needs are far from sufficient.…”
Section: Discussion: Towards Future Ndc Cyclesmentioning
confidence: 99%
See 2 more Smart Citations
“…King, 2016;Levin et al, 2015;. Moreover, the relatively positive responses on technical and financial support provided to developing countries to implement their NDCs are quite different from, for instance, Pauw, Castro, Pickering, and Bhasin (2019a), whose work suggested that current financing needs are far from sufficient.…”
Section: Discussion: Towards Future Ndc Cyclesmentioning
confidence: 99%
“…For the respondents to our surveys, knowledge and capacity limitations formed clear obstacles when preparing the NDCs. 63% of the respondents to Survey 1 (n = 48) agreed with the statements that they had difficulties in assessing the financial and support needs for implementing their NDC (see Pauw et al, 2019a, for a detailed analysis of support needs in NDCs). Sixty-one per cent perceived difficulties in assessing economic impacts and co-benefits to be a problem, and 35% found assessing levels of fairness and ambition a challenge.…”
Section: Knowledge and Capacitymentioning
confidence: 99%
See 1 more Smart Citation
“…The above does not take into account to what extent the implementation of contributions is dependent on external support (see Section 3.2) as it is out of the scope of this study. Zimm and Nakicenovic (2019) and Pauw et al (2019) analyse the implications of conditionality on feasibility and equity of NDC implementation in more detail.…”
Section: Resultsmentioning
confidence: 99%
“…However, the notions of equity and CBDR-RC in the UNFCCC are not limited to mitigation (UN, 1992, Article 3.1). Considerations of equity should therefore encompass other elements of international climate policy, such as vulnerability to climate impacts, finance, and technology transfer (BASIC Experts, 2011; Climate Action Network, 2013; Klinsky and Winkler, 2014;Pauw et al, 2014).…”
mentioning
confidence: 99%